Mental Process in The Mother Poem (A Systemic Functional Linguistic Analysis) - Sabitah Salsabila (ELITE: Journal of English Language and Literature, 2016)
Everyone has different kinds of emotions. Every emotion that is expressed can have an impact on a person's actions. In other words, everyone in an emotional situation is trying to send a message to others, either by action or by language. The objective of this research is to describe the mental process depicted in Gwendolyn Brooks' poem, the Mother. This research focuses on the mental process, which includes aspects of feeling, wanting, thinking, and seeing. There is a senser, a process, and a phenomenon in mental processes that can be used. This mental process might be interpreted as either flowing from or impinging on a person's consciousness. Halliday's Systemic Functional Linguistics is used to analyze each line of the Mother poem as data. The descriptive qualitative method was used in this research. The data for this analysis were gathered by reading, comprehending, previewing, and coding, and then analyzed by presenting, describing, and interpreting the data, as well as concluding the results of the analysis. As a result of the analysis, the researcher found eight data, four data for thinking (cognitive), three data for emotion (affective), and one data for perception. The cognitive process is the most dominant because the poet conveys her thoughts and realizations about the abortion she committed. There were six websites used in this research such as bachelorandmaster.com, aresearchguide.com, shmoop.com, literarydevices.net, poemanalysis.com, and shareyouressays.com, as tools to help the researcher understand each line of the Mother’s poem meaning.